The road to sustainable transport - Banister, D (Witan Media Ltd, 2015)
The transport sector stands out in its lack of progress in reducing emissions. Radical new approaches are required if the sector is to achieve the necessary 60 per cent reduction by 2050. Transport is central to society. Production, business, leisure, as well as everyday activities, all depend on movement. Global mobility has been built on efficient aviation and shipping networks, enhanced by the new communications technologies. At the more local level, there have also been substantial increases in mobility using all forms of transport as income levels have risen. The Sustainable Mobility Paradigm (SMP) is intended to shift thinking by encouraging lower levels of mobility and shorter distances within cities, as well as promoting more efficient low-carbon transport. It is also concerned with the creation of spaces and localities that are attractive and affordable, as neighbourhood quality is central to sustainable mobility.